2014
DOI: 10.1002/chem.201402595
|View full text |Cite
|
Sign up to set email alerts
|

Highly Functionalized and Potent Antiviral Cyclopentane Derivatives Formed by a Tandem Process Consisting of Organometallic, Transition‐Metal‐Catalyzed, and Radical Reaction Steps

Abstract: A simple modular tandem approach to multiply substituted cyclopentane derivatives is reported, which succeeds by joining organometallic addition, conjugate addition, radical cyclization, and oxygenation steps. The key steps enabling this tandem process are the thus far rarely used isomerization of allylic alkoxides to enolates and single-electron transfer to merge the organometallic step with the radical and oxygenation chemistry. This controlled lineup of multiple electronically contrasting reactive intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…An initial screening of new redox isomerization catalysts 12 revealed that the catalyst system consisting of [Ru(p-cymene)Cl 2 ] 2 and P(OMe) 3 as a ligand 9 is most efficient at accomplishing the critical isomerization of alkoxide 3 to enolate 4 in quantitative yield and the shortest possible reaction time (see the ESI, Table S1 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial screening of new redox isomerization catalysts 12 revealed that the catalyst system consisting of [Ru(p-cymene)Cl 2 ] 2 and P(OMe) 3 as a ligand 9 is most efficient at accomplishing the critical isomerization of alkoxide 3 to enolate 4 in quantitative yield and the shortest possible reaction time (see the ESI, Table S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…They served well in a unique tandem organometallic addition of aryllithium reagents 1 to α,β-unsaturated aldehydes 2/redox isomerization of resulting alkoxide 3 to enolate 4/Michael addition to 5/radical cyclization/oxygenation process, providing diverse highly functionalized cyclopentane derivatives 6. 9 Based on our experience in merging polar and radical processes, 10 we hypothesized that a bioinspired radical-based modular strategy may provide a very short access to tetrahydrofuran lignans III. We envisaged a tandem process consisting of nucleophilic addition of substituted aryllithiums 1 to unsaturated aldehydes 2 and subsequent redox isomerization of resulting alkoxides, thus generating enolates 4.…”
Section: Introductionmentioning
confidence: 99%
“…The Herrera group demonstrated that normally hard to functionalize methyl groups can be easily activated for cyclizations to pyrrolidines by the iodine/iodobenzene diacetate reagent system [127]. Antiviral cyclopentane derivatives became easily accessible by new complex tandem reactions consisting of polar organometallic additions coupled with radical cyclizations and oxygenations [128,129] and a new approach toward the total synthesis of bridged diketopiperazine alkaloids using the persistent radical effect emerged [130]. Alternatively, the central diazabicyclo[2.2.2]octane core of several alkaloids can be approached by reaction sequences proceeding through single electron transfer (SET) oxidation steps, thus switching among multiple intermediate types of different oxidation state in one pot [131].…”
Section: Working Group 4: Bio-inspired Synthetic Strategiesmentioning
confidence: 99%
“…Enolates formed in this way underwent addition to Michael acceptors followed by radical cyclization and oxygenation with TEMPO. 38 These methodologies were applied to the syntheses of natural products, such as isoprostanes. 39 Oxidative enolate dimerization promoted by the ferrocenium ion has been applied in the synthesis of the lomaiviticin family of natural products, which display potent cytotoxic activity.…”
Section: Review Syn Thesis Scheme 18mentioning
confidence: 99%